Relationship Between Back Pain and Job Satisfaction among Teachers in Kelantan - Nor Amirah, Mohamed @ Mohd Ghazali; Naresh Bhaskar, Raj; Mohd Haidzir, Manaf (INTI International University, 2023)
Back pain is one of the most common health problems experienced among individuals, particularly among those who have jobs that require them to sit, stand or perform physically demanding activities for long hours. Teachers are one such group of professionals who are at higher risk of developing back pain due to the nature of their jobs. This has been acknowledged as a significant problem that can impact the job satisfaction of the teaching profession. This study aimed to identify the relationship between back pain and job satisfaction among teachers. This study examines on how back pain is related to the level of job satisfaction among teachers in Kelantan. A cross-sectional study was conducted among randomly selected teachers from thirty-four primary schools in Tanah Merah, Kelantan from December to February 2023. The level of lower back pain was assessed using an Oswestry Low Back Pain Disability, while for Teacher satisfaction scale (TJSS) was used to examine the teacher satisfaction level. The response rate of this study was 100% (n=208). The majority of respondents are females (n=170,81.7%), Malay(n=174,83.7%), married(n=163,78.4%), aged between 30- 39 years old(n=64,31.3%),40-49 years old(n=119,57.2%) and have more than 10 years of work experience. The level of back pain and job satisfaction among teachers (r=-.129, 95%CI=1.6970, 1.9059, P-value= .064) were no significant correlation between two variables. There is insufficient evidence to conclude that back pain among teachers is directly related to job satisfaction. Teaching may be physically stressful and teachers often experience high levels of stress and burnout. However, the findings on relationship between back pain and job satisfaction are not related.